Research progress on VARROA DESTRUCTOR - Chen Yuxin (BIO Web of Conferences, 2022)
Varroa destructor is the most serious threat for western honeybees worldwide. It parasitizes mostly on honeybee's pupae and larvae, resulting in impaired development, decreased immunity, residual wings, loss of flight ability, and even direct death. At the same time, it can cause a series of diseases, greatly infesting bee colonies. This paper introduces the classification, distribution and biological characteristics of Varroa destructor, and discusses its transmission mode, harm form and common control measures.